Approved recurrent estimates of east central states of Nigeria 1971-72 - East Central States (Enugu East central state of Nigeria, 1972)
Approved recurrent estimates of East Central State of Nigeria ... (including Memorandum, Budget speech and Statutory Corporations).".
aia 29/03 2019
Loans
Keywords: East Central State; Budget - Nigeria-; Appropriations and Expenditures; Nigeria